Development and tests of sliding contact line-powered track transporter - Jiang, Yihua; Yang, Fang; Zhang, Zihao; Li, Shanjun (International Journal of Agricultural and Biological Engineering, 2023)
In order to solve the problems of complexity of control systems and the limited power supply of traditional fuel-powered and battery-driven transporters operating in mountainous orchards, a sliding contact line-powered track transporter was designed and manufactured based on theoretical calculations. Key components of the transporter were developed such as a PLC-based (programmable logic controller) control system, a sliding contact power supply, and transmission system, and a position limit device. The functions and performance of designed transporter were tested. The test results showed that the transporter exhibited a high stability of operation with an average operation velocity of 0.70 m/s, the maximum working slope of 48°, the maximum load of 400 kg, and the maximum remote control distance reaching 1482 m. When the power supply circuit of sliding contact line was 108.8 m in length, the maximum voltage drop was 2.4 V, and the maximum power loss was 174.72 W, which were close to the theoretical calculation values. With a single power supply cabinet, the transporter can operate normally for a maximum track distance of 175.69 m. All the technical indicators of the transporter met the design requirements, and the above-mentioned problems such as complexity of the control system and limited energy supply of the traditional mountain orchard transporter were well solved. This study can provide reference for the design and optimization of mountain orchard transporter. Keywords: mountain orchard, transporter, remote control, sliding contact line, voltage drop DOI: 10.25165/j.ijabe.20231604.7841 Citation: Jiang Y H, Yang F, Zhang Z H, Li S J. Development and tests of sliding contact line-powered track transporter. Int J Agric & Biol Eng, 2023; 16(4): 68–75.